The Effects of Behavioral Foundations and Business Strategy on Corporate Dividend Policy - Liao, Wen-Ju; Lin, Yu-En; Li, Xin-Zhe; Chih, Hsiang-Hsuan (Frontiers in Psychology, 2022)
This study analyzes the influence of behavioral foundation factors and corporate strategic behavior on the formulation of corporate dividend policy. We use the Logit model and the OLS model for estimating the empirical model. The year- and industry-fixed effects are controlled in the model. We consider the behavioral foundations in three dimensions-ambiguity aversions, risk aversion, and loss aversion. The results show firms with high ambiguity or high risk infrequently pay dividends but firms with loss-averse behavior tend to pay dividends. This paper also provides evidence that a firms’ business strategy influences its corporate dividend policy. Aggressive firms inhibit the payout of dividends. In additional tests, we find the results remain unchanged in those firms with high corporate governance or high growth opportunities.